The role of financial literacy for Business Sustainability at PT Olam Makassar - Ambar Arum, Ruki (International Journal of Educational Research & Social Sciences, 2021)
The objective of this scientific paper is to understand the role of financial literacy for Business Sustainability at PT Olam Makassar.  This scientific paper used descriptive qualitative method which described the observation and interview results. To get data, the writer observed and interviewed the employees of PT Olam Makassar which resposible for  financial literacy for Business Sustainability. The result of the research obtained such as : the role of financial literacy for Business Sustainability implemented and related elements to the financial literacy for Business Sustainability at PT Olam Makassar. Based on the research, it can be concluded that by having knowledge about good financial literacy, one can make sustainable business concept, therefore its business sustainability can be maintained.